C-Phycocyanin and Phycocyanobilin as Remyelination Therapies for Enhancing Recovery in Multiple Sclerosis and Ischemic Stroke: A Preclinical Perspective - Giselle Pentón-Rol; Javier Marín-Prida; Viviana Falcón-Cama (Behavioral Sciences, 2018)
Myelin loss has a crucial impact on behavior disabilities associated to Multiple Sclerosis (MS) and Ischemic Stroke (IS). Although several MS therapies are approved, none of them promote remyelination in patients, limiting their ability for chronic recovery. With no available therapeutic options, enhanced demyelination in stroke survivors is correlated with a poorer behavioral recovery. Here, we show the experimental findings of our group and others supporting the remyelinating effects of C-Phycocyanin (C-PC), the main biliprotein of Spirulina platensis and its linked tetrapyrrole Phycocyanobilin (PCB), in models of these illnesses. C-PC promoted white matter regeneration in rats and mice affected by experimental autoimmune encephalomyelitis. Electron microscopy analysis in cerebral cortex from ischemic rats revealed a potent remyelinating action of PCB treatment after stroke. Among others biological processes, we discussed the role of regulatory T cell induction, the control of oxidative stress and pro-inflammatory mediators, gene expression modulation and COX-2 inhibition as potential mechanisms involved in the C-PC and PCB effects on the recruitment, differentiation and maturation of oligodendrocyte precursor cells in demyelinated lesions. The assembled evidence supports the implementation of clinical trials to demonstrate the recovery effects of C-PC and PCB in these diseases.